بحث ميداني لعوامل البيئة التنظيمية المحددة لتوقع السلوك الإبداعي بين الموظفين - عابدي, محمد السعيد (جامعة الوادي - University of Eloued, 2023)
يعتبر تشخيص البيئة التنظيمية ممارسة شائعة في جميع المؤسسات لفهم العوامل والأبعاد التي تنبئ بالإبداع وأبعاده، وهذا بعد تراجع المنظور الفردي الصارم في الإبداع، وتزايد منحى الاهتمام بالبيئة التي يعمل فيها الموظفين، وما يحيط بهم من ظروف مواتية توفر لهم الفرص والوقت للتجريب. لهذا، يفترض البحث أن التنبؤ بالإبداع (التفكير والسلوك الإبداعي) وكذلك عدم الإبداع (عدم الرغبة وعدم القدرة على الإبداع) يعتمد في الغالب على عوامل البيئة التنظيمية (ظروف ومحتوى العمل). لاختبار هذا الافتراض، تم الاستناد إلى تحليل توجهات وأراء عينة من (100) موظف ينتمون إلى (34) مؤسسة جزائرية، باستخدام الأدوات الإحصائية المعروفة، حيث أثبت اختبار الانحدار المتعدد مدى تفسير أو تحديد النتائج الايجابية والسلبية للإبداع من قبل عوامل البيئة التنظيمية. The diagnosis of the organizational environment is a common practice in organizations to understand the factors and dimensions that predict creativity. after the strict individual perspective on creativity has receded, the attention has been shifted to the environment in which the creative individual works. Therefore, the research assumes that predicting creativity (creative thinking and behavior) as well as non-creativeness (unwillingness and inability to be creative) mostly depends on the factors of the organizational environment (conditions and content of work). To test this assumption, a sample of (100) employees from (34) Algerian organizations has been used to analyze how far positive and negative consequences of creativity are explained or determined by factors of the organizational environment
Applied research of organizational environment factors to predict creative behavior among employees
مقال
Keywords: البيئة التنظيمية؛ ظروف العمل؛ محتوى العمل؛ الإبداع؛ التفكير الإبداعي.; Organizational environment; Work conditions; Job content; Creativity; Creative thinking .